Health Counseling and Cervical Cancer Screening Test for Reproductive Age Women in Bojong Gede District : Penyuluhan Kesehatan Deteksi Dini Kanker Serviks pada Wanita Usia Subur di Kecamatan Bojong Gede - Shinta Novelia; Bunga Tiara Carolin (KHD Production, 2023)
In Indonesia, 75% of women have experienced vaginal discharge at least once in their lives and half of them have experienced vaginal discharge twice or more. Vaginal discharge is a classic problem for most women. Ironically, most women do not know about vaginal discharge and the causes of vaginal discharge. If not handled properly, vaginal discharge can be fatal, infertility and ectopic pregnancy (pregnancy outside the womb) can be one of the consequences of vaginal discharge. The early symptoms of uterine cancer usually start with vaginal discharge. The betel leaf (Piper betle linn) used in this study belongs to the Peiperaceae family. The part used is the leaves. Betel leaf contains essential oils that contain compounds that have strong antibacterial properties, which are referred to as